KONUSLÍQ KÓPOBRAZLÍQTÍŃ KÓLEMIN KOMPYUTER BAǴDARLAMALARÍNDA ESAPLAW USÍLLARÍ HAQQÍNDA - Qutbaev, A.B. (SCIENCE and SOCIETY, 2026)
In this work, methods for computing volumes of cone manifolds for knots in hyperbolic geometry are presented, along with differences between computations performed in the computer programs SnapPy and Wolfram Mathematica 13.2.